Perbedaan Kadar Gula Darah Berdasarkan Jenis Kelamin dan Status Gizi (IMT) Lansia Penderita Diabetes Melitus Tipe 2 - Reksi Umbu Remu Samapati; Ronasari Mahaji Putri; Hilda Mazarina Devi (Universitas Baiturrahim, 2023)
One disease that often attacks old age is type 2 DM. The number of DM cases is increasing. Differences in gender and nutritional status (BMI) in blood sugar levels in elderly patients with type 2 diabetes at the Dinoyo Community Health Center, Malang City, were the aims of this research. Cross-sectional design and observational methods characterized this study. questionnaire-based data collection using a sample of 32 people selected using the quota sampling method. Man Whitney test was used to analyze the collected data. The results of the research showed that female respondents experienced an incidence of diabetes of (59.4%) and respondents who had an obese nutritional status experienced an incidence of diabetes of (93.8%); There are differences in blood sugar based on gender (p value = 0.007) and nutritional status (p value = 0.000) in elderly people suffering from type 2 DM at the Dinoyo Community Health Center, Malang City. It is hoped that future researchers will examine the role of the family which is associated with the incidence of type 2 DM